Reinterpreting the Nature-Culture Dichotomy in Colin Thiele's Storm Boy and Its 2019 Film Adaptation: An Ecocritical Adaptation Study: Iadat Tawil Thunaiyyat al-Tabiah wa al-Thaqafah fi Riwayat Fata al-Asifah li Colin Thiele wa Iqtibasiha al-Sinamai Am 2019: Dirasah Iqtibasiyyah fi al-Naqd al-Bii - Rinahayu, Nuril; Masnia Rahayu (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This article examines how the 2019 film adaptation of Colin Thiele's Storm Boy (1964) reconstructs the nature-culture dichotomy through changes in characterisation, focalisation, and cinematic narration. Using a qualitative descriptive method, the study compares the novel with Shawn Seet's Storm Boy (2019) and analyses selected scenes that foreground Michael Kingley's relation to pelicans, Fingerbone Bill, coastal space, and industrial development. The analysis is framed by ecocriticism, Hutcheon's theory of adaptation, and Boggs and Petrie's concepts of film analysis. The findings show that the novel depicts Michael as a child whose daily life is integrated with the coastal environment, while the film repositions him as an elderly industrial figure whose childhood memories interrupt his involvement in a coastal development project. Through flashback structure, images of rain, pelicans, urban buildings, and Fingerbone's ecological knowledge, the film transforms a children's story of animal rescue into a critique of anthropocentrism, commodification, and modern society's separation from nature. The adaptation therefore does not merely reproduce the novel; it reinterprets its ecological meaning for a context shaped by climate anxiety and industrial expansion. This study contributes to ecocritical adaptation studies by showing how adaptation can expand a literary environmental narrative into a contemporary critique of socio-ecological change. تتناول هذه المقالة كيفية إعادة بناء الثنائية بين الطبيعة والثقافة في الاقتباس السينمائي الصادر عام 2019 لرواية كولن ثيلي Storm Boy الصادرة عام 1964، وذلك من خلال التغييرات في بناء الشخصيات، والتبئير، والسرد السينمائي. وباستخدام المنهج الوصفي النوعي، تقارن الدراسة بين الرواية وفيلم Storm Boy للمخرج شون سيت عام 2019، كما تحلل مشاهد مختارة تُبرز علاقة مايكل كينغلي بالبجع، وفينغربون بيل، والفضاء الساحلي، والتنمية الصناعية. تستند الدراسة في تحليلها إلى النقد البيئي، ونظرية الاقتباس عند هتشيون، ومفاهيم بوغز وبيتري في تحليل الفيلم. وتُظهر النتائج أن الرواية تصوّر مايكل بوصفه طفلًا مندمجًا في حياته اليومية مع البيئة الساحلية، في حين يعيد الفيلم تقديمه بوصفه شخصية صناعية مسنة تتقاطع ذكريات طفولتها مع تورطه في مشروع تنمية ساحلية. ومن خلال بنية الاسترجاع الزمني، وصور المطر، والبجع، والمباني الحضرية، والمعرفة البيئية التي يمتلكها فينغربون، يحوّل الفيلم قصة أطفال عن إنقاذ الحيوانات إلى نقد للمركزية البشرية، وتسليع الطبيعة، وانفصال المجتمع الحديث عنها. وبذلك، فإن الاقتباس لا يكتفي بإعادة إنتاج الرواية، بل يعيد تفسير معناها البيئي في سياق يتشكل بفعل القلق المناخي والتوسع الصناعي. تسهم هذه الدراسة في دراسات الاقتباس من منظور النقد البيئي من خلال إظهار كيف يمكن للاقتباس أن يوسّع السرد الأدبي البيئي ليصبح نقدًا معاصرًا للتحولات الاجتماعية والبيئية. Artikel ini mengkaji bagaimana adaptasi film tahun 2019 dari novel Storm Boy karya Colin Thiele yang terbit pada tahun 1964 merekonstruksi dikotomi alam dan budaya melalui perubahan dalam karakterisasi, fokalisasi, dan narasi sinematik. Dengan menggunakan metode deskriptif kualitatif, penelitian ini membandingkan novel tersebut dengan film Storm Boy karya Shawn Seet tahun 2019 serta menganalisis beberapa adegan terpilih yang menonjolkan hubungan Michael Kingley dengan burung pelikan, Fingerbone Bill, ruang pesisir, dan pembangunan industri. Analisis dalam penelitian ini dibingkai melalui pendekatan ekokritik, teori adaptasi Hutcheon, serta konsep analisis film Boggs dan Petrie. Temuan penelitian menunjukkan bahwa novel menggambarkan Michael sebagai seorang anak yang kehidupan sehari-harinya menyatu dengan lingkungan pesisir, sementara film memosisikannya kembali sebagai tokoh industri yang telah lanjut usia, yang ingatan masa kecilnya mengganggu keterlibatannya dalam proyek pembangunan kawasan pesisir. Melalui struktur kilas balik, citra hujan, burung pelikan, bangunan perkotaan, dan pengetahuan ekologis Fingerbone, film ini mengubah kisah anak-anak tentang penyelamatan hewan menjadi kritik terhadap antroposentrisme, komodifikasi, dan keterpisahan masyarakat modern dari alam. Dengan demikian, adaptasi tersebut tidak sekadar mereproduksi novel, tetapi menafsirkan ulang makna ekologisnya dalam konteks yang dibentuk oleh kecemasan iklim dan ekspansi industri. Penelitian ini berkontribusi pada kajian adaptasi berbasis ekokritik dengan menunjukkan bagaimana adaptasi dapat memperluas narasi lingkungan dalam karya sastra menjadi kritik kontemporer terhadap perubahan sosial-ekologis.